Work Agility in the Disruptive Era: The Role of Locus of Control in Female Employees of SOEs - Andi Ririn Oktaviani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In an era of disruption characterized by rapid change and high complexity, work agility is key to organizational success, especially for female employees in a State-Owned Enterprise (SOEs) in Makassar. Therefore, this study aims to examine the effect of knowledge transfer and technological support on work agility, with psychological determinants as a mediating variable. The method used involved 100 female SOEs employees selected using purposive sampling. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results showed that knowledge transfer and technological support significantly improved employees' psychological determinants; these psychological determinants, in turn, had a significant positive effect on work agility. Knowledge transfer had no direct effect on work agility, while technological support showed a marginal direct effect. These findings confirm that psychological determinants mediate the relationship between knowledge transfer and technological support on work agility. Practically, this study recommends developing a knowledge-sharing culture, effective technology utilization, and enhancing psychological resources to create an adaptive and resilient workforce.